1973
DOI: 10.1063/1.1661972
|View full text |Cite
|
Sign up to set email alerts
|

Photostimulated exoelectron emission from slip lines: A new microscopy of metal deformation

Abstract: Exoelectron emission from abraded metal surfaces in the darkIn this paper we show that photostimulated exoelectron emission resulting from the plastic deformation of a metal originates solely from the slip lines produced on the surface. Conclusive evidence is provided by micrographs formed by direct electron optical imaging of the exoelectrons. The exoelectrons are emitted only from bare metal revealed by a localized rupturing of the natural surface oxide during the formation of the slip step. This contrast me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…[34][35][36] Deformation in aluminum alloys is largely confined to slip on well-defined planes. [1][2][3][4][5][6][7][8][9] Prior to strain localization, at a constant crosshead speed, the sample area is expected to increase linearly as fresh metal surface is produced (almost) uniformly along the gauge section.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36] Deformation in aluminum alloys is largely confined to slip on well-defined planes. [1][2][3][4][5][6][7][8][9] Prior to strain localization, at a constant crosshead speed, the sample area is expected to increase linearly as fresh metal surface is produced (almost) uniformly along the gauge section.…”
Section: Discussionmentioning
confidence: 99%
“…The photoelectron intensities increase considerably during plastic deformation due to the production of new metal surface area where slip lines and bands intersect the surface. 34,35 The distribution of the crystal structures for these newly formed surfaces will in general differ from the distribution of crystal structures prior to deformation, especially in the presence of grain rotation. Thus we expect that deformation will also alter the photoelectron-energy distributions as deformation proceeds.…”
Section: Introductionmentioning
confidence: 98%
“…17,18,[28][29][30][31][32][33][34][35][36][37][38][39][40] Electron microscopy, autoradiographic stripping, 29 and photoemission spectroscopy 17,37 showed that these signals were closely associated with the formation of slip lines and bands on deformed surfaces. 17,18,[28][29][30][31][32][33][34][35][36][37][38][39][40] Electron microscopy, autoradiographic stripping, 29 and photoemission spectroscopy 17,37 showed that these signals were closely associated with the formation of slip lines and bands on deformed surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to stress that the increase in the PSE signal during deformation is proportional to the area of fresh metal surface exposed as slip lines and bands intersect the surface, 17 with possibly minor effects due to grain rotation. The tendency of the native oxide on aluminum to hinder PSE allows for sensitive measurements of the formation of new surface area.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of TSEE and optically stimulated exoelectron emission (OSEE) to dosimetric applications has been pointed out by Becker [ 1,2]. The emission phenomena are also utilized currently as a research tool in solid state physics in order t,o detect structural defects in metals [3,4]. By means of the TSEE dosimetry using CaSO,, a linear response has been obtained down to 3x 10-"Rad or less [5].…”
Section: Introductionmentioning
confidence: 99%